Pengaruh Electronic Word of Mouth dan Brand Awareness Terhadap Keputusan Pembelian: Studi pada Pengguna Parfum HNMS di Tiktok - Siti Nurjannah; Dadan Abdul Aziz Mubarok (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
This study aims to assess the impact of Brand Awareness (e-WOM) and Brand Awareness on the purchasing decisions of HNMS Perfume consumers on TikTok. Advances in technology have led to a widespread shift towards online shopping via social commerce platforms such as TikTok Shop, which provides convenient access, diverse product options, and intensive promotional activities. In the digital age, e-WOM as a means of consumer-to-consumer communication and Brand Awareness as the level of brand recognition are critical elements influencing purchase decisions. The research employs quantitative methods with both descriptive and verification approaches. Primary data was collected through questionnaires distributed to 100 TikTok users who are familiar with or have purchased HNMS Perfume products. The sampling method utilized non-probability sampling with purposive criteria, targeting respondents aged 20-40 years, who own TikTok accounts, and have made at least two purchases. The results demonstrate that both Brand Awareness and Brand Awareness variables exert a positive and significant influence on purchasing decisions, whether considered separately or together. The study concludes that consumers should take into account e-WOM information and Brand Awareness when making purchase decisions to ensure the products chosen meet their needs. Keywords: Brand Awareness , Brand awareness, Purchase Decision, TikTok Shop, HNMS Perfume